Testing potential new sites for optical telescopes in Australia - Hotan, Claire Elizabeth (Curtin University, 2010)
In this study we aim to find locations in Australia capable of hosting a large optical telescope, ideally larger than our current premier instrument, the 3.9m Australian Astronomical Telescope, which may be built in the future to extend Australia's optical astronomy capabilities and create multi-wavelength ties with radio astronomy.We are able to refine possible locations by studying remotely sensed meteorological data to ascertain expected cloud coverage rates across Australia, and combining them with a digital elevation model using a Geographic Information System software package. We find that the best sites in Australia for building optical telescopes are likely to be on the highest mountains in the Hamersley Range in Northwest Western Australia, while the MacDonnell Ranges in the Northern Territory may also be appropriate.The current major optical astronomy site in Australia, Siding Spring, is good considering its proximity to major cities, but being located near the Great Dividing Range it experiences relatively high levels of cloud cover. We believe, however, that similar seeing values should be available and with more observing time at the proposed sites. We thus propose that a campaign of astronomical site testing should be undertaken on Mount Bruce and Mount Meharry in the Hamersley Range, and seeing and light pollution values compared to those measured at existing observatory sites.